Development of a crack cutting method for glass plates used for flat panel displays. (7th June 2006) - Suzuki, Kiyoshi; Shishido, Yoshiaki; Koga, Nobuhiro; Shirai, Takeki; Iwai, Manabu; Uematsu, Tetsutaro
In this paper, a high precision breaking method for brittle materials by indentation using an inclined pyramid type indenter is proposed. It was reported that for an indentation angle of θ = 3°, a crack occurs straight in the inclination direction along the diagonal corners of the indent even for a single indent, and the probability of occurrence of the crack is rather high even for low loading. In this paper, the fracture coefficient distribution, the qualitative measurement of crack propagation and propagation position of the indentation are obtained from the FEM analysis. Intermittent indentation using an indenter with an indentation angle of θi = 3° at an interval of d = 30 mm along the ridge direction was performed. As a result, the connection between adjacent cracks along the diagonal could be achieved. On breaking the glass panel, a good surface could be obtained. Finally a prototype of the scribing machine based on the research esults was manufactured and was found to work satisfactorily.